O itinerário enquanto instrumento de preservação do patrimônio cultural: o caso da Estrada Real - Flavia Mosqueira Possato (2012)
This dissertation has as its goal, to think over the instrument of the Cultural Routes, recently introduced in the field of cultural heritage, searching comprehension on its amplitude and efficiency. For so, it was taken as reference mainly on Unesco actions on acknowledging the world heritage, showing how this international agency has dealt with the theoretical and practical challenges imposed by an idea such as cultural routes. To approach the cultural routes, we will show, to begin with, its relation with another idea, also recently introduced in the area, the cultural landscape, that is, among the itineraries, also brings the relation nature, culture. It is notorious that the idea of an itinerary brings back the importance of the values and the meaning of each one of the cultural properties to the social and human development, proving that this instrument can be an important mechanism of territorial managing towards the sustainable development, when it includes its cultural, social, environmental, political and economic dimensions. To acknowledge the high potential of this instrument, it took place a study case, about the Estrada Real, as an itinerary that goes from Rio de Janeiro to Minas Gerais, involving the old paths that were used to occupy Brazilian territory. The conclusion was, even though it presents several cultural properties throughout the Caminhos Reais, its actual management turns it incompatible with its needs to be acknowledge as a cultural routes. For another side, to acknowledge, through a specific multidisciplinary analysis, the touristic potential of Estrada Real, the speech points the need of deeper technical and scientific study in order to improve this proposal.